2021
DOI: 10.3892/mco.2021.2475
|View full text |Cite
|
Sign up to set email alerts
|

Associations between matrix metalloproteinase, tissue inhibitor of metalloproteinase and collagen expression levels in the adjacent rectal tissue of colorectal carcinoma patients

Abstract: As the commonest type of cancer in Europe and the third most common type of cancer worldwide, colorectal carcinoma (CRC) poses a challenge for numerous scientific studies. At present, the cause of this disease is remains to be elucidated, but early diagnosis is only one solution to prevent serious health complications. As a structural scaffold, the extracellular matrix (ECM) is in direct contact with tumour cells and significantly interferes with tumour progression. During the process of tumorigenesis, the ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Furthermore to gastric cancer, research results from several researchers have revealed that many collagen-encoding genes, including COL1A2 and COL3A1 had higher expression levels in pancreatic cancer 88 , thyroid cancer 89 and esophageal cancer 90 . Dibdiakova et al’s 91 results demonstrated that COL3A1 expression was significantly higher in CRC tissues compared to normal tissues, are consistent with the results of experiments from our findings. According to Tang et al 56 COL3A1 has been demonstrated to be overexpressed in stage IV colorectal cancer and to be significantly downregulated in lung metastasis samples compared to liver metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore to gastric cancer, research results from several researchers have revealed that many collagen-encoding genes, including COL1A2 and COL3A1 had higher expression levels in pancreatic cancer 88 , thyroid cancer 89 and esophageal cancer 90 . Dibdiakova et al’s 91 results demonstrated that COL3A1 expression was significantly higher in CRC tissues compared to normal tissues, are consistent with the results of experiments from our findings. According to Tang et al 56 COL3A1 has been demonstrated to be overexpressed in stage IV colorectal cancer and to be significantly downregulated in lung metastasis samples compared to liver metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…TIMP4 is a member of a family of extracellular matrix metalloproteinase inhibitors that has been shown to modulate processes such as cell differentiation, proliferation, and apoptosis [ 74 ]. TIMP4 is overexpressed in several cancers, including colorectal, and its expression was found to correlate with longer patient survival (in rectal cancer) [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of the extracellular matrix (ECM) is crucial for tumor mass growth and cell invasion, creating space for malignant cells to migrate [ 14 ]. The matrix metalloproteinases (MMPs) and their inhibitors (TIMPs) play a pivotal role in this process, not limited to CNS tissue [ 15 , 16 ]. The MMP family comprises 23 endopeptidases that catalyze the degradation of the ECM and the basal membrane [ 17 ].…”
Section: Introductionmentioning
confidence: 99%